Recycling of spent adsorbents for oxyanions and heavy metal ions in the production of ceramics. (November 2015) - Verbinnen, Bram; Block, Chantal; Van Caneghem, Jo; Vandecasteele, Carlo
Highlights: Traditional disposal methods for spent adsorbents have a high environmental impact. Recycling them as raw material for ceramics production is a valuable alternative. Mo leaching was reduced after production of ceramics with 3% addition of adsorbent. Heavy metal leaching was reduced after ceramics production with spiked raw material. Addition of spent adsorbents can also improve structural and aesthetic properties. Abstract: Spent adsorbents for oxyanion forming elements and heavy metals are classified as hazardous materials and they are typically treated by stabilization/solidification before landfilling. The use of lime or cement for stabilization/solidification entails a high environmental impact and landfilling costs are high. This paper shows that mixing spent adsorbents in the raw material for the production of ceramic materials is a valuable alternative to stabilize oxyanion forming elements and heavy metals. The produced ceramics can be used as construction material, avoiding the high economic and environmental impact of stabilization/solidification followed by landfilling. To study the stabilization of oxyanion forming elements and heavy metals during the production process, two series of experiments were performed. In the first series of experiments, the main pollutant, Mo was adsorbed onto iron-based adsorbents, which were then mixed with industrial sludge (3 w/w%) and heated at 1100 °C for 30 min. Mo was chosen, as this element is easily adsorbed onto iron-based adsorbents and it is the element that is the most difficult to stabilize (i.e. the highest temperatures need to be reached before the concentrations in the leachate are reduced). Leaching concentration from the 97/3 sludge/adsorbent mixture before heating ranged between 85 and 154 mg/kg; after the heating process they were reduced to 0.42–1.48 mg/kg. Mo was actually stabilized, as the total Mo concentration after addition was not affected by the heat treatment. In the second series of experiments, the sludge was spiked with other heavy metals and oxyanion forming elements (Cr, Ni, Cu, Zn, As, Cd and Pb) in concentrations 5 times higher than the initial concentrations; after heat treatment the leachate concentrations were below the regulatory limit values. The incorporation of spent adsorbents in ceramic materials is a valuable and sustainable alternative to the existing treatment methods, saving raw materials in the ceramics production process and avoiding the use of stabilizing agents. Besides, spent adsorbents added to the raw material for ceramic products, may improve their aesthetic and structural properties.